The relationship between countermovement jump force-time characteristics and 2,000-m rowing ergometer performance - DeLeo, J. M.; Wolf, A.; Philipp, N. M.; Ackerman, K. E.; Fry, A. C. (Frontiers in Sports and Active Living, 2025)
Background: Rowing is a strength-endurance sport. The Olympic race distance of 2,000-m (2k) requires extensive aerobic and anaerobic energy system contributions, along with sustained high force output.